The impact of rater experience and essay quality on the variability of EFL writing scores - Şahan, Özgür (Taylor and Francis, 2019)
This chapter addresses a research gap by examining raters with varying levels of experience. It investigates the variability of ratings assigned to English as a foreign language (EFL) essays of different qualities in Turkish higher education by raters with varying levels of experience. Raters gave similar scores to high-quality essays but varied in their scores given to low-quality EFL essays. Given that assessing students’ EFL writing performance in higher education plays an important role in students’ academic careers, ensuring reliability to provide students with fair judgments is essential in tertiary education in Turkey. The variation among raters while assessing high-quality essays suggests a fairness problem in EFL assessment for student writers with better writing abilities. EFL writing is offered as a separate course in different forms, such as advanced writing or academic writing, in the preparatory programs and English major departments, and students’ progress is evaluated through in-term and end-of-term exams.